2003
DOI: 10.5034/inquiryjrnl_40.3.269
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Medicaid Primary Care Case Management on Office-Based Physician Supply in Alabama and Georgia

Abstract: The success of the ''primary care case management (PCCM)'' form of managed care implemented in many state Medicaid programs over the past several years depends in part on the expanded availability of primary care physician sites to substitute for hospital-based outpatient care and to provide a medical home for enrollees. However, the PCCM requirement for physicians to accept assignment of a caseload of patients and to provide all of their primary care likely conflicts with the approach of limited Medicaid part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 8 publications
2
13
0
Order By: Relevance
“…Our work extends earlier analysis of the effects of PCCM on participating providers in the two study states (Adams, Bronstein, and Florence 2003); this work found reductions in the proportion of participating physicians, reductions in small Medicaid practices, and declines in Medicaid visit volume among those still participating. We make methodological contributions by controlling for these changes in the availability of participating providers in the child's community and using fixed effects to control for time-invariant characteristics of the children as we follow them over the pre/post-PCCM implementation period.…”
Section: New Contributionmentioning
confidence: 68%
See 3 more Smart Citations
“…Our work extends earlier analysis of the effects of PCCM on participating providers in the two study states (Adams, Bronstein, and Florence 2003); this work found reductions in the proportion of participating physicians, reductions in small Medicaid practices, and declines in Medicaid visit volume among those still participating. We make methodological contributions by controlling for these changes in the availability of participating providers in the child's community and using fixed effects to control for time-invariant characteristics of the children as we follow them over the pre/post-PCCM implementation period.…”
Section: New Contributionmentioning
confidence: 68%
“…Indirect effects are those that may occur with changes in the availability-the number and relative proximity-of Medicaid participating physicians and clinics. Earlier work found that PCCM implementation was associated with reductions in participating physicians, the number of small Medicaid practices, and participating physicians' volume, but effects differed across Georgia and Alabama and urban/rural areas (Adams, Bronstein, and Florence 2003).…”
Section: Conceptual Model and Background Conceptual Modelmentioning
confidence: 98%
See 2 more Smart Citations
“…In the past decade, several states have implemented primary care case management in their Medicaid programs. 8 One of the main rationales for primary care case management was to provide a primary care physician to Medicaid beneficiaries to improve the continuity of care and to reduce reliance on the ED for nonurgent care. Private health plans have also attempted to reduce ED use in recent years by increasing copayments for ED visits.…”
mentioning
confidence: 99%